On the Capacity of SWIPT Systems with a Nonlinear Energy Harvesting Circuit - Morsi, Rania; Jamali Kooshkghazi, Vahid; Ng, Derrick Wing Kwan; Schober, Robert (IEEE International Conference on Communications (ICC), 2018)
In this paper, we study information-theoretic limits for simultaneous wireless information and power transfer (SWIPT) systems employing a practical nonlinear radio frequency (RF) energy harvesting (EH) receiver. In particular, we consider a three-node system with one transmitter that broadcasts a common signal to separated information decoding (ID) and EH receivers. Owing to the nonlinearity of the EH receiver circuit, the efficiency of wireless power transfer depends significantly on the waveform of the transmitted signal. In this paper, we aim to answer the following fundamental question: What is the optimal input distribution of the transmit waveform that maximizes the rate of the ID receiver for a given required harvested power at the EH receiver? In particular, we study the capacity of a SWIPT system impaired by additive white Gaussian noise (AWGN) under average-power (AP) and peak-power (PP) constraints at the transmitter and an EH constraint at the EH receiver. Using Hermite polynomial bases, we prove that the optimal capacity-achieving input distribution that maximizes the rate-energy region is unique and discrete with a finite number of mass points. Our numerical results show that the rate-energy region is enlarged for a larger PP constraint and that the rate loss of the considered SWIPT system compared to the AWGN channel without EH receiver is reduced by increasing the AP budge
Keywords: AWGN channels; channel capacity; decoding; energy harvesting; optimisation; polynomials; radio receivers; radiofrequency power transmission; telecommunication power supplies; rate-energy region; nonlinear energy harvesting circuit; information-theoretic limits; wireless power transfer; SWIPT system; nonlinear radio frequency energy harvesting receiver; information decoding; additive white Gaussian noise; average-power constraint; peak-power constraint; Hermite polynomial; simultaneous wireless information and power transfer; Receivers; Radio frequency; Integrated circuit modeling; Rectennas; Transmitters; RF signals; AWGN channels